The Effect of Sales Growth and Leverage on Tax Avoidance Empirical Study of Coal Sub-Sector Mining Companies Listed on the Indonesia Stock Exchange in 2014-2018 - Nadya, Bella; Purnamasari, Dyah (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
This study aims to determine the influence of sales growth and leverage on tax avoidance on coal sub-sector mining companies listed on the IDX in 2014-2018. The data used were secondary data and the samples were financial statements from 10 coal sub-sector mining companies listed on the IDX in 2014-2018. The method of sample selection was purposive sampling, while the data analysis included panel data regression analysis. The data were analyzed using Eviews 10 software. The results of this study show that sales growth and leverage affect tax avoidance. Suggestions for further research is to add research model variables that influence tax avoidance.